Surgeons' involvement in COVID-19 treatment: a practice by a regional core hospital in Japan to avoid physician burnout - Yugo Matsui; Siyuan Yao; Takashi Kumode; Keisuke Tanino; Ryosuke Mizuno; Yusuke Ogoshi; Shusaku Honma; Teppei Murakami; Takatsugu Kan; Sanae Nakajima; Takehisa Harada; Koji Oh; et al. (BMC, 2023)
Abstract Background To prevent task accumulation on certain divisions, our institution developed a unique system of allocating inpatient treatment of COVID-19 patients to doctors who were not specialized in respiratory infections. The objective of this study was to investigate whether surgeons can be involved in the COVID-19 inpatient treatment without negatively affecting patient outcome, and how such involvement can affect the wellbeing of surgeons. Methods There were 300 patients diagnosed with COVID-19 and hospitalized from January to June 2021, and 160 of them were treated by the redeployed doctors. They were divided into 3 groups based on the affiliation of the treating doctor. Patient characteristics and outcomes were compared between the groups. In addition, the impact of COVID-19 duty on participating surgeons was investigated from multiple perspectives, and a postduty survey was conducted. Results There were 43 patients assigned to the Department of Surgery. There were no differences in the backgrounds and outcomes of patients compared with other groups. The surgeon's overtime hours were significantly longer during the duty period, despite no change in the number of operations and the complication rate. The questionnaire revealed that there was a certain amount of mental and physical burden from the COVID-19 duty. Conclusion Surgeons can take part in inpatient COVID-19 treatment without affecting patient outcome. However, as such duty could negatively affect the surgeons' physical and mental wellbeing, further effort is needed to maintain the balance of fulfilling individual and institutional needs.